Correlation between hardness and SEM-EDS characterization of palm oil waste based biocoke - Asri, Gani; Erdiwansyah, .; Hera, Desvita; Saisa, .; Mahidin, .; Rizalman, Mamat; Zulhaini, Sartika; Ratna Eko, Sarjono (KeAi Communications Co., 2024)
This research investigates the relationship between hardness and microstructure obtained through SEM-EDS analysis of palm oil waste-based biocoke. The mechanical qualities and chemical composition of biocoke are being studied concerning the influence of temperature conditions. The manufacturing temperature of biocoke may vary between 150 °C and 190 °C. Utilizing SEM-EDS, we were able to characterize the microstructure and analyze the elemental composition, while the Hardness Shore D approach was used for the most complex materials. These results highlight the possibility of optimizing production temperature to produce biocoke with better mechanical performance. They show a positive correlation between biocoke hardness and structured carbon content. At 150 °C and 180 °C, respectively, the EFB biocoke reached its maximum hardness level of 62 ± 5. At 190 °C, OPM biocoke generated a 60 ± 5 times greater hardness than that of OPM and OPF biocoke. The OPT biocoke sample had the highest porosity with a score of 0.86, or 85.76%. Furthermore, compared to EFB biocoke, OPM and OPF biocokes had a priority of 0.84 (84.20%) and 0.83 (83.48%), respectively. Biocoke hardness is a quality indicator of physical and chemical qualities; the vital link between biocoke hardness, structural features, and elemental composition supports this idea.